2008
DOI: 10.1161/circulationaha.107.756494
|View full text |Cite|
|
Sign up to set email alerts
|

Angioplasty Strategies in ST-Segment–Elevation Myocardial Infarction

Abstract: ardiovascular disease is the most common cause of mortality in most developed nations; Ϸ838 000 inhospital discharges in the United States in 2005 were for acute myocardial infarction, 29% to 47% of which were acute ST-segment-elevation myocardial infarction (STEMI). 1 The case fatality rate of STEMI has fallen dramatically in the last 3 decades, in part because of the widespread use of reperfusion therapy. 1-4 STEMI is in most cases due to rupture of an inflamed thin-capped fibroatheroma containing a lipid-ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 149 publications
(123 reference statements)
0
25
0
1
Order By: Relevance
“…Baseline and clinical characteristics were compared between STB and DTB patient groups by 2 , analysis of variance, and Wilcoxon rank-sum test. Clinical outcomes of 30-day all-cause mortality and 90-day all-cause mortality were reported in 99.7% of patients with missing 90-day survival status in only 15 patients.…”
Section: Study Design and Statistical Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Baseline and clinical characteristics were compared between STB and DTB patient groups by 2 , analysis of variance, and Wilcoxon rank-sum test. Clinical outcomes of 30-day all-cause mortality and 90-day all-cause mortality were reported in 99.7% of patients with missing 90-day survival status in only 15 patients.…”
Section: Study Design and Statistical Analysismentioning
confidence: 99%
“…1,2 Compared with fibrinolytic therapy, primary PCI establishes Thrombolysis in Myocardial Infarction (TIMI) flow grade 3 in 80% to 95% of patients, significantly lowers the risk of intracranial hemorrhage, and offers more robust survival advantage in higherrisk patients with cardiogenic shock, severe heart failure, or unstable arrhythmias. 2,3 Multiple randomized clinical studies also have demonstrated the superiority of rapid primary PCI over fibrinolysis in STEMI.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Además, este protocolo no requiere el uso profiláctico de anti-histamínicos ni esteroides, pero debe ser realizado en condiciones vigiladas, idealmente en una unidad monitorizada y con equipamiento de reanimación adecuado en caso de requerirse. Evidentemente, un esquema de desensibilización de este tipo no debiera retardar la atención adecuada de los pacientes que se presentan con un infarto con supradesnivel del segmento ST, situación en la cual la intervención coronaria inmediata ha mostrado un enorme impacto pronóstico 11 . En estos pacientes, tal como ocurrió con el individuo del caso 3, se ha probado con éxito la desensibilización en los días posteriores al evento 9 .…”
Section: Discussionunclassified
“…The development of percutaneous coronary intervention (PCI) has enhanced the management of patients with acute coronary syndrome, and the prognosis of these patients has been considerably improved [8][9][10][11][12][13][14][15] . However, in patients with stable coronary artery disease, coronary revascularization decreases angina symptoms but does not significantly prevent cardiac death or myocardial infarction [16][17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%